Frecuencia de escherichia coli productoras de betalactamasas aisladas en urocultivos de pacientes del centro salud aranjuez Trujillo, la libertad, 2013 - Yupanqui Díaz, Cinthia Melissa (2016)
In this investigation was determined the frequency of Escherichia coli producing betalactamases isolated from urine cultures of patients attending Center Salud Aranjuez Trujillo, La Libertad, 2013. The urine culture is a method used to support the diagnosis of Urinary Tract Infections (UTI), in which the number and type of bacteria is identified in urine. Samples were seeded in agar Mac Conkey and blood agar incubating at 37°C for 24 hours. Cultures of Escherichia coli were identified by morphological and cultural characteristics of the colonies; finding a frequency of isolation of 47% of 468 samples of urine cultures, analyzed statistically was not significant (P>0,05). 220 Escherichia coli cultures isolated classical betalactamase and extended spectrum betalactamase and was detected by iodometric technique and double diffusion plate, respectively; finding a frequency of 31,8% classic betalactamase and extended spectrum betalactamase 6,8%; these values were evaluated statistically highly significant, in both (P<0,05). As for the production of extended spectrum betalactamase of Escherichia coli cultures 15 in relation to the numbers of combinations of antibacterial used as ceftazidime, cefuroxime, aztreonam and cefotaxime, applying Chi square test we found that there is significant difference (P<0,05) in their pattern of resistance, presenting aztreonam and cefotaxime like the antimicrobials greater contribution to the test, with 11 and 9 resistant crops, respectively.